2005
DOI: 10.1111/j.1365-2249.2005.02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance in the production between vascular endothelial growth factor and endostatin in Kawasaki disease

Abstract: SummaryTo investigate whether an imbalance exists in the production between angiogenic and antiangiogenic growth factors in patients with Kawasaki disease (KD), we measured the serum levels of vascular endothelial growth factor (VEGF) and endostatin (ES) in 35 patients with KD, 15 patients with acute febrile diseases (disease controls) and 15 healthy children. KD patients had significantly higher VEGF levels and lower ES levels ( P < < < < 0·01) in the acute and subacute phases than the disease control and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The imbalance between VEGF (a stimulator of angiogenesis) and endostatin (an inhibitor of angiogenesis) has been demonstrated in many benign conditions other than diabetic retinopathy [39,65] such as ischemic heart disease [66], rheumatoid arthritis [67], emphysema [68], Kawasaki disease [67,69], ulcerative colitis [70], and neoplastic diseases as colorectal cancer [40], renal cancer [41], pituitary adenoma [71], breast cancer [72], and both primary [73] and metastatic [74] liver tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between VEGF (a stimulator of angiogenesis) and endostatin (an inhibitor of angiogenesis) has been demonstrated in many benign conditions other than diabetic retinopathy [39,65] such as ischemic heart disease [66], rheumatoid arthritis [67], emphysema [68], Kawasaki disease [67,69], ulcerative colitis [70], and neoplastic diseases as colorectal cancer [40], renal cancer [41], pituitary adenoma [71], breast cancer [72], and both primary [73] and metastatic [74] liver tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reports on the correlation between the endostatin and the cerebral ischemia, some studies have revealed the role of endostatin in other angiogenesis-dependent diseases such as atherosclerosis, Kawasaki disease and ischemic heart disease [22][23][24] . In addition, the serum endostatin has been reported to increase in several types of malignant tumor [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that dysregulation of angiogenesis plays a role in the vasculopathy of the disease (4, 5). However, studies of the pathologic changes in the vessel wall of KD patients have been hampered by the fact that tissue samples are rare due to the low mortality rate and the inability to sample coronary arteries in living children.…”
mentioning
confidence: 99%